2008
DOI: 10.3233/jad-2008-13206
|View full text |Cite
|
Sign up to set email alerts
|

Park2-Null/Tau Transgenic Mice Reveal a Functional Relationship between Parkin and Tau

Abstract: Mutations, haplotypes, and polymorphisms of tau and Park-2 genes constitute risk factors for developing tauopathies. In order to analyze the possible relationship between parkin and tau we generated a double-mutant mouse deficient for Park-2 expression and overexpressing a mutant tau protein (hTauVLW). Mice develop normally, although the median survival rate is considerably reduced with respect to wild type (45%). Aggregates of phosphorylated tau in neurons and reactive gliosis are quite abundant in cortex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…This is consistent with the reported significant association of homozygous V380 with sporadic PD [L€ ucking et al, 2003]. As a functional relationship between Parkin and tau existed [Guerrero et al, 2008], the reported association of 380L with less risk of taupathy progressive supranuclear palsy [Ros et al, 2008] also suggests the functional significance of this variation. Further studies are needed to clarify if and how this polymorphism predisposes to PD.…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with the reported significant association of homozygous V380 with sporadic PD [L€ ucking et al, 2003]. As a functional relationship between Parkin and tau existed [Guerrero et al, 2008], the reported association of 380L with less risk of taupathy progressive supranuclear palsy [Ros et al, 2008] also suggests the functional significance of this variation. Further studies are needed to clarify if and how this polymorphism predisposes to PD.…”
Section: Discussionsupporting
confidence: 80%
“…[12,13] The most common tauopathy is Alzheimers disease, but tau deposits also occur in frontotemporal dementias , Picks disease, Parkinsons disease, progressive nuclear palsy, and other conditions. [14,15] In Alzheimers disease, the brain contains two types of aggregates: intracellular neurofibrillary tangles (tau protein) and extracellular senile or "amyloid" plaques consisting of the Ab peptide, a cleavage product of the membrane protein APP. [16] Both types of aggregates are toxic for neurons, and both are based on the principle of amyloid aggregation, in which fibers are formed from the subunit protein by axial stacking of b strands, generating a cross-b-sheet structure at the core of the filaments.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, KaplanMeier survival analysis using the Park2 tm1Roo knockout model suggested an increase in mortality, which is consistent with data from PD patients' pre-L-DOPA therapy (RodriguezNavarro et al, 2007). However, in another study using the Park2 tm1Roo knockout model on a different background a difference in survival was not found (Guerrero et al, 2008). A reduction in body weight was identified in three lines but was not replicated in three other lines (Table 2) (Itier et al, 2003;Oyama et al, 2010;Palacino et al, 2004;Perez and Palmiter, 2005;Von Coelln et al, 2004;Zhu et al, 2007).…”
Section: Behavioural Characteristicsmentioning
confidence: 99%